1998
DOI: 10.1088/0954-3899/24/9/013
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of muons at sea level

Abstract: We measure muon intensities at sea level by using the OKAYAMA cosmic-ray telescope in detail. Measured muons are also contained in the low-momentum region where they are strongly affected by geomagnetic field effects including the east-west effect. We report the zenith and azimuthal angular dependence of conventional muons in the momentum range 1.5-250 GeV/c in the zenith angular range 0 • -81 • . S Tsuji et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 29 publications
(68 reference statements)
3
30
0
Order By: Relevance
“…In these simulations, 500 000 muons were injected into the modeled radiation shields (50 cm thick lead and 30 cm thick stainless steel plates) according to an energy spectrum measured within an angle range between 60 and 70 • from zenith (Achard et al, 2004;Tsuji et al, 1998;Abdel-Monem et al, 1975). The lowest muon energy considered in the simulation was 1 GeV, which corresponded to the cutoff energy derived from the detectors and the shields.…”
Section: Background Estimationmentioning
confidence: 99%
“…In these simulations, 500 000 muons were injected into the modeled radiation shields (50 cm thick lead and 30 cm thick stainless steel plates) according to an energy spectrum measured within an angle range between 60 and 70 • from zenith (Achard et al, 2004;Tsuji et al, 1998;Abdel-Monem et al, 1975). The lowest muon energy considered in the simulation was 1 GeV, which corresponded to the cutoff energy derived from the detectors and the shields.…”
Section: Background Estimationmentioning
confidence: 99%
“…For the geometrical factor calculations it was assumed that there was no variation of the muon intensity over the acceptance angle. The effect on the geometrical factor due to the intensity variation was examined using the measured muon spectra [22] and the observed zenithal distribution in our apparatus in the rigidity range 0.2 to 1.5 GV/c at ground. We found that the calculated geometrical factor would be reduced by about 3%.…”
Section: E Systematic Uncertaintiesmentioning
confidence: 99%
“…On the above calculations it was assumed that there is no variation of the muon intensity over the acceptance angle. The effect on the geometrical factor due to the intensity variation was examined using the measured muon spectra [16] and the observed zenithal distribution in our apparatus in the rigidity range 0.2 to 1.5 GV. We found that the calculated geometrical factor would be reduced by about 3%.…”
mentioning
confidence: 99%